Anemia and Associated Factors among Public Elementary School Children in Asella Town, Southeast Ethiopia: A Facility-Based Cross-Sectional Study - Ararso Hordofa Guye; Kasim Hansa; Kasahun Ketema; Meseret Moroda; Dame Banti Shambi (Anemia)
Background. Anemia has a negative impact on school children, including poor physical growth and reduced mental performance. Children show poor attentiveness, behavior, and memory and reduced school performance. There is limited evidence of the magnitude of anemia and associated factors in school-age children in Ethiopia, including the study area. Objective. To assess the magnitude of anemia and associated factors among public elementary school children in Asella Town, Southeast Ethiopia, in 2022. Methods. A school-based cross-sectional study was conducted in Asella Town from April 5 to May 5, 2022. A total of 442 school children aged 7–14 years were included in the study using the multistage sampling method. Data were collected using a pretested and semistructured questionnaire through a face-to-face interview technique. The hemoglobin concentration was determined by using the HemoCue 301+ analyzer. Anthropometric data and stool examinations were collected from participants. Data were entered into EpiData version 4.6, transported, and analyzed by Statistical Package for Social Sciences version 26. Bivariable and multivariable logistic regression analyses were carried out. Adjusted odds ratios along with their 95% confidence interval were used, and a p value of ≤0.05 was used for declaring statistical significance. Results. A total of 435 students with a mean age and standard deviation of 10.77 ± 2.21 years participated in the study. The magnitude of anemia was 78 (17.9%), with a 95% CI (14.3, 21.47). Of the participants, 63 (14.5%) were mild anemic and 15 (3.4%) were moderately anemic. Children whose mothers have no formal education (AOR = 3.94, 95% CI: 1.89, 8.21), underweight children (AOR = 3.83, 95% CI: 1.98, 7.40), and parasites in their stool (AOR = 3.72, 95% CI: 1.50, 9.20) were significantly associated with anemia in school-age children. Conclusion. Anemia among school-age children was found to be a mild public health problem. Uneducated mothers, intestinal parasite infections, and underweight children were found to be determinants of anemia among school-age children. Health professionals should provide health education for mothers about child-feeding practices and the consumption of dietary sources of iron.